Niosomes: A Revolutionary Approach for Skin Cancer Treatment - Padave, Aditi P.; Rane, Bhushan R.; Jain, Ashish S. (Current Nanomedicine, 2025)
Skin cancer is one of the most common types of cancer globally, with melanoma and non-melanoma being the two primary forms. Melanoma tends to be less frequent but more dangerous, while non-melanoma types, including squamous and basal cell carcinoma, are more prevalent. Caucasian populations are at a higher risk of developing skin cancer due to their skin's susceptibility to ultraviolet (UV) radiation. According to recent data, skin cancer ranks as the seventeenth most common cancer worldwide. An emerging approach to treating skin conditions, including skin cancer, is using niosomes, an advanced drug delivery system. Niosomes are vesicles made from non-ionic surfactants, stabilized by cholesterol, that encapsulate drugs. They have gained prominence because they address several issues related to traditional topical treatments, such as poor solubility, instability, low bioavailability, and rapid drug breakdown. This review article focuses on the use of niosomes in dermatology, particularly for drug delivery through the skin. Niosomes offer several distinct advantages, making them an ideal choice for topical drug delivery. Their unique structure allows them to transport both water-soluble and fat-soluble drugs effectively. Additionally, they enhance drug permeation through the skin, improve drug stability, and allow for extended drug release. These properties make niosomes a valuable tool in clinical settings, providing potential benefits for a range of skin-related therapies. With their growing popularity, niosomes are shaping the future of innovative and more efficient topical drug delivery methods.
Keywords: melanoma